Mike Meyers' CompTIA A+ guide to managing and troubleshooting PCs (exams 220-901 & 220-902) - Meyers, Mike 1961- (McGraw-Hill Education, 2016)
Essential Skills for a Successful IT Career Written by the leading authority on CompTIA A+ certification and training, this four-color guide will help you become a certified IT professional with proven expertise in hardware and software, and help you pass CompTIA A+ exams 220-901 and 220-902. Mike Meyers' CompTIA A+ Guide to Managing and Troubleshooting PCs, Fifth Edition offers complete coverage of the latest exam objectives. You'll get on-the-job tips, end-of-chapter review questions, and hundreds of color photographs and illustrations. Learn how to: Work with CPUs, RAM, microprocessors, BIOS, motherboards, power supplies, and other PC components Install, configure, and troubleshoot hard drives Manage peripheral devices and removable media Install, upgrade, and maintain operating systems, including Windows, Mac OS X, and Linux Troubleshoot common computer problems Establish users and groups Set up video and multimedia cards Administer smartphones, tablets, and other mobile devices Install and configure wired and wireless networks Connect to the Internet Secure your PC and your network Install, configure, and manage printers and multifunction devices Work with the latest virtualization technologies Understand safety and environmental issues Electronic content includes: Practice exams for 901 & 902 One hour+ of free video training from Mike Meyers TotalSim simulations of performance-based questions Mike's favorite free PC tools and utilities A complete PDF copy of the book Instructor resources available: Instructor's Manual Power Point slides for each chapter with photographs and illustrations from the book Test Bank cartridges with hundreds of questions for use as quizzes and exams Answers to the end of chapter sections are not included in the book and are only available to adopting instructors.
Includes index. - Description based on online resource; title from title page (viewed June 30, 2016)
Keywords: Computing Technology Industry Association -- Study guides -- Examinations; Microcomputers -- Study guides -- Maintenance and repair -- Examinations; Computer technicians -- Certification; Computing Technology Industry Association; Micro-ordinateurs; Entretien et réparations; Examens; Guides de l'étudiant; Computer technicians; Certification; Examinations; Microcomputers; Maintenance and repair; Examinations; Study guides